2020
DOI: 10.3390/genes11111336
|View full text |Cite
|
Sign up to set email alerts
|

DNMTs and Impact of CpG Content, Transcription Factors, Consensus Motifs, lncRNAs, and Histone Marks on DNA Methylation

Abstract: DNA methyltransferases (DNMTs) play an essential role in DNA methylation and transcriptional regulation in the genome. DNMTs, along with other poorly studied elements, modulate the dynamic DNA methylation patterns of embryonic and adult cells. We summarize the current knowledge on the molecular mechanism of DNMTs’ functional targeting to maintain genome-wide DNA methylation patterns. We focus on DNMTs’ intrinsic characteristics, transcriptional regulation, and post-transcriptional modifications. Furthermore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 126 publications
0
19
0
1
Order By: Relevance
“…It plays a major role in a variety of biological and molecular processes during embryonic development including X-chromosome inactivation, genomic imprinting, transcription, chromatin organization and chromosome stability [1-3 � ]. 5mC is established by the DNA methyltransferases (DNMTs) [1,2,4] and removed either catalytically by the Ten Eleven Translocation (TET) proteins or passively by dilution over cellular divisions in absence of maintenance [5,6].…”
Section: -Methylcytosine (Or 5mcmentioning
confidence: 99%
“…It plays a major role in a variety of biological and molecular processes during embryonic development including X-chromosome inactivation, genomic imprinting, transcription, chromatin organization and chromosome stability [1-3 � ]. 5mC is established by the DNA methyltransferases (DNMTs) [1,2,4] and removed either catalytically by the Ten Eleven Translocation (TET) proteins or passively by dilution over cellular divisions in absence of maintenance [5,6].…”
Section: -Methylcytosine (Or 5mcmentioning
confidence: 99%
“…DNMT3 plays a central role in epigenetic modifications of the genome via DNA methylation [ 84 ]. Barrès and colleagues showed that, in skeletal muscle from patients with T2DM, DNMT3-related non-CpG hypermethylation occurred in the PGC-1α promoter, which resulted in decreased PGC-1α gene expression and mtDNA levels [ 85 ].…”
Section: Mitochondria and Pgc-1α In Wat During Obesity Or Crmentioning
confidence: 99%
“…For instance, TETs loss of function is associated with genome wide hypomethylation [ 7 ]. DNA methylation is initiated by a special histone marks pattern, by proteins that bind methylated DNA, by tissue-specific transcription factors [ 8 ]. Several studies have revealed many transcription factors that can interact with DNMT1 and DNMT3a/3b DNA methyltransferases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%